Lakosságcsere - Pozsonyi, Péter (Hungary : MTV - Hungarian Television, 2007)
A film about President Edvard Beneš’ decision to create a Czechoslovakian nation-state which led to the expulsion of Hungarians living in Upper Hungary to Bohemia in February 1947.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films